Zinc phthalocyanine loaded- antibody functionalized nanoparticles enhance photodynamic therapy in monolayer (2-D) and multicellular tumour spheroid (3-D) cell cultures - Simelane, Nokuphila Winifred Nompumelelo; Abrahamse, Heidi (Frontiers in Molecular Biosciences, 2024)
In conventional photodynamic therapy (PDT), effective delivery of photosensitizers (PS) to cancer cells can be challenging, prompting the exploration of active targeting as a promising strategy to enhance PS delivery. Typically, two-dimensional (2-D) monolayer cell culture models are used for investigating targeted photodynamic therapy. However, despite their ease of use, these cell culture models come with certain limitations due to their structural simplicity when compared to threedimensional (3-D) cell culture models such as multicellular tumour spheroids (MCTSs). In this study, we prepared gold nanoparticles (AuNPs) that were functionalized with antibodies and loaded with tetra sulphonated zinc phthalocyanine (ZnPcS4). Characterization techniques including transmission electron microscopy (TEM) was used to determine the size and morphology of the prepared nanoconjugates. TEM micrographs revealed small, well distributed, and spherical shaped nanoparticles. We also conducted a comparative investigation to assess the photodynamic effects of ZnPcS4 alone and/or conjugated to the bioactively functionalized nanodelivery system in colorectal Caco-2 cells cultured in both in vitro 2-D monolayers and 3-D MCTSs. Our results demonstrated that biofunctional nanoparticles mediated PDT significantly inhibited cell proliferation and induced apoptosis in Caco-2 cancer monolayers and, to a lesser extent, in Caco-2 MCTSs. Live/dead assays further elucidated the impact of actively targeted nanoparticles-photosensitizer nanobioconjugate, revealing enhanced cytotoxicity in 2-D cultures, with a notable increase in dead cells post-PDT. In 3-D spheroids, however, while the presence of nanoparticles facilitated improved therapeutic outcomes, the live/ dead results showed a higher number of viable cells after PDT treatment compared to their 2-D monolayer counterparts suggesting that MCTSs showed more resistance to PS drug as compared to 2-D monolayers. These findings suggest a high therapeutic potential for the multifunctional nanoparticles as a photosensitizer nanodelivery system for colorectal cancer PDT. Furthermore, the choice of cell culture model influenced the response of cancer cells to PDT treatment, highlighting the feasibility of using MCTSs for targeted PS delivery to colorectal cancer cells.